2009
DOI: 10.1111/j.1468-3083.2009.03242.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological burden of anogenital warts

Abstract: Psychological aspect of anogenital warts should not be neglected. Patient's education about HPV infection and their consequences should be emphasized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
10
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 14 publications
3
10
0
6
Order By: Relevance
“…These results reflect the emotional distress caused by GW that has been found in several studies around the world [2,19,29,30]. A greater distress in women with external GW lesions is aligned with previous observations where the psychological impact of a sexually transmitted disease diagnosis (regardless of which one) seems to be greater in women than in men [31].…”
Section: Discussionsupporting
confidence: 88%
“…These results reflect the emotional distress caused by GW that has been found in several studies around the world [2,19,29,30]. A greater distress in women with external GW lesions is aligned with previous observations where the psychological impact of a sexually transmitted disease diagnosis (regardless of which one) seems to be greater in women than in men [31].…”
Section: Discussionsupporting
confidence: 88%
“…A similar but lesser impact of GW on HRQoL has been demonstrated in men in a study using the initial 22-item CECA questionnaire [47]. When stratified by sex in the present study, the difference between GW and history of GW continued to be observed in women, but not in men.…”
Section: Discussionsupporting
confidence: 86%
“…In a study surveying quality of life in men diagnosed with anogenital warts, men expressed concern about contagiousness and showed inadequate knowledge about their diagnosis. (14, 15) Studies in college students have generally found low levels of knowledge about HPV infection in male participants. (16) In a survey of men who have sex with men (MSM) treated at a sexually transmitted disease (STD) clinic, men who knew someone diagnosed with HPV were knowledgeable of transmission, but overall most patients were unaware of HPV risk or potential modes of transmission.…”
Section: Introductionmentioning
confidence: 99%